2019
DOI: 10.1108/ijchm-02-2018-0105
|View full text |Cite
|
Sign up to set email alerts
|

Does hotel cleanliness correlate with surfaces guests contact?

Abstract: Purpose This study aims to strengthen implications about hotel cleaning outcomes by comparing guests’ perception of the amount of contact they have with cleanliness of hotel surfaces. Design/methodology/approach This study used two data-collection methods, a survey and an adenosine triphosphate (ATP) test. Data were collected from recent hotel guests using Amazon Mechanical Turk. Guests were asked to identify hotel surfaces that they touch most frequently. Actual hotel cleanliness was measured using empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 50 publications
2
29
0
2
Order By: Relevance
“…Many studies have considered overall hygiene and cleanliness as a principal determinant of travelers' hotel choices (Lockyer, 2005), guest satisfaction (Gu and Ryan, 2008), guest delight (Magnini et al, 2011), and guest loyalty (Barber and Scarcelli, 2010). However, scholars have rarely considered the hygiene and cleanliness of specific areas in a hotel (Park et al, 2019). The present paper thus recommends that researchers move beyond typical perspectives on the antecedents and outcomes of hotel hygiene and cleanliness to delve into guests' perceptions of the cleanliness of hotel surfaces (e.g., key cards, bed linens, light switches, and TV remotes) and other areas (e.g., air conditioning systems).…”
Section: Hygiene and Cleanlinessmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have considered overall hygiene and cleanliness as a principal determinant of travelers' hotel choices (Lockyer, 2005), guest satisfaction (Gu and Ryan, 2008), guest delight (Magnini et al, 2011), and guest loyalty (Barber and Scarcelli, 2010). However, scholars have rarely considered the hygiene and cleanliness of specific areas in a hotel (Park et al, 2019). The present paper thus recommends that researchers move beyond typical perspectives on the antecedents and outcomes of hotel hygiene and cleanliness to delve into guests' perceptions of the cleanliness of hotel surfaces (e.g., key cards, bed linens, light switches, and TV remotes) and other areas (e.g., air conditioning systems).…”
Section: Hygiene and Cleanlinessmentioning
confidence: 99%
“…The present paper thus recommends that researchers move beyond typical perspectives on the antecedents and outcomes of hotel hygiene and cleanliness to delve into guests' perceptions of the cleanliness of hotel surfaces (e.g., key cards, bed linens, light switches, and TV remotes) and other areas (e.g., air conditioning systems). As noted, hotel surfaces receiving frequent human contact are more likely to be contaminated through touch (Park et al, 2019) and become sources of transmission of infectious diseases such as COVID-A more granular understanding of hotel cleanliness will assist hoteliers in streamlining their housekeeping procedures to ensure effective cleaning and sanitization of hotel properties.…”
Section: Hygiene and Cleanlinessmentioning
confidence: 99%
“…Amid the explored physical servicescape factors, in recent research, cleanliness has been shown to have a noteworthy positive influence on customer satisfaction and loyalty (Lockyer, 2003;Park et al, 2019;Zemke et al, 2015). In the wake of COVID-19 and rising hygienic concerns, cleanliness is believed to be prominent physical evidence that can be considered an element of the service environment that requires management and updating to maintain sales and avoid customer dissatisfaction (Jiang and Wen, 2020).…”
Section: Ijchm 335mentioning
confidence: 99%
“…For example, cleanliness is one of the factors influencing the selection of accommodation services where the risk of contamination by various viruses and bacteria still stays even if the hotel premises are cleaned properly (Zemke et al, 2015). For many years, researchers have been found investigating the significance of effective housekeeping systems and how this contributes to customer satisfaction but, with an increase in global travel, the importance of effective cleaning has been amplified manifolds (Park et al, 2019). Following regular and detailed cleaning/sanitation practices have become even more vital amidst this COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%